A biomechanical analysis of walking and running on a treadmill in different level of inclined surfaces - Mohammad Shahril, Salim; Fatin Nadia, Maknoh; Nurhidayah, Omar; Muhamad Khairul, Ali Hassan (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/